ENERGOECONOMICS OF ELECTRICAL DRIVES FOR WASTE WATER AERATION UNITS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
This article discusses essential aspects of Induction motor’s (IM) selection for reconstruction projects of waste water purification plants as well eventual saving o f electric power in waste water pneumatic aeration units by using regurable electrical drives. Experience has proven that it is almost always cost effective to raplace old unefficient motor with new energy efficient and reliable unit. Anyway economical calculations must be perform. The paper considers methods and results o f economic effect calculation from energy savings in three phase IM dependent on their efficiency, power factor, operation time and reliability. The higher the motor’s energetic indices, the higher the effect from electrical energy saving and the lower the payment time of additional charges. Most electric power is consumed during waste water pneumatic aeration because it is an uninterrupted process. Analysis of the biological oxygen need for communal waste water purification prove that the medium required air blower’s productivity is 50- 60% of maximum value. Therefore the regulation of air blowers by using frequency converter is vitally important for energy saving and profitability o f communal waste water biological purification plants. Calculations show that use of reguable air blower with frequency converter is profitable for medium and large scale purification plants. The payment time of the additional charges for frequency converter and automation are about 2 years and lower if the rated power of air blower’s electrical drive is 15 kW and higher, but medium energy saving exceeds 30% in comparison with rated value.